Hubungan Türkiye-Israel dengan Partai Keadilan dan Pembangunan (AKP), di bawah Bayangan Hamas - Erdurmaz, Ali Serdar; Bagci, Huseyin (Jurnal ICMES, 2024)
Turkish-Israeli relations during the AKP era have been tumultuous, shaped by ideological disparities, internal politics, and regional shifts. Despite these hurdles, both nations have maintained pragmatic cooperation, notably in trade, energy, and security domains. This study delves into the evolution of Turkish-Israeli ties, analysing key factors influencing their dynamics. It explores how cooperation persists amid ideological rifts and assesses the impact of recent normalisation efforts and ongoing tensions. Employing a conceptual and chronological approach, the research unveils a pattern of alternating between strategic collaboration and strained relations. The Mavi Marmara raid, a significant event in the history of Turkish-Israeli relations, marked a point of severe strain. However, economic exchanges have thrived, and recent attempts at normalisation offer hope despite the challenges that remain, notably Turkiye's support for Hamas and divergent regional policies. Meanwhile, various factors have shaped the relationship between Turkiye and Hamas over the past two decades. Key influences include the Palestinian issue, ideological alignments and tensions, regional dynamics, and, notably, the significant impact of individual leaders, such as President Erdoğan. Turkiye's engagement with Hamas has evolved from facilitating dialogue to providing political and financial support, especially following Hamas's electoral victory in 2006. Despite occasional tensions, Turkiye sees Hamas as a legitimate representative of the Palestinian people and supports it as part of its broader strategy to challenge the status quo in the Middle East. However, Turkiye's support for Hamas has strained its relations with Israel and raised concerns among Western allies, highlighting the complexities of Turkiye's role in the Israeli-Palestinian conflict. This article will evaluate Turkish-Israel relations within the new approach toward the Hamas.